2019
DOI: 10.1101/690230
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phase variation of a signal transduction system controlsClostridioides difficilecolony morphology, motility, and virulence

Abstract: 23di-GMP, biofilm 2 24 Abstract 25Recent work has revealed that Clostridioides difficile, a major cause of nosocomial diarrheal 26 disease, exhibits phenotypic heterogeneity within a clonal population as a result of phase 27 variation. Many C. difficile strains representing multiple ribotypes develop two colony 28 morphotypes, termed rough and smooth, but the biological implications of this phenomenon 29 have not been explored. Here, we examine the molecular basis and physiological relevance 30 of the distinct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 85 publications
(115 reference statements)
0
11
0
Order By: Relevance
“…Another c-di-GMP-responsive riboswitch, Cdi2_2, precedes the genes encoding the signal transduction system CmrRST in C. difficile , where CmrS is a putative histidine kinase, and CmrR and CmrT are two predicted response regulators [ 181 ]. Binding of c-di-GMP to Cdi2_2 positively affects cmrRST expression [ 182 ], most likely through anti-termination of transcription. Interestingly, cmrRST is also regulated by phase variation with an invertible DNA sequence, the cmr switch, located upstream of the corresponding genes [ 182 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another c-di-GMP-responsive riboswitch, Cdi2_2, precedes the genes encoding the signal transduction system CmrRST in C. difficile , where CmrS is a putative histidine kinase, and CmrR and CmrT are two predicted response regulators [ 181 ]. Binding of c-di-GMP to Cdi2_2 positively affects cmrRST expression [ 182 ], most likely through anti-termination of transcription. Interestingly, cmrRST is also regulated by phase variation with an invertible DNA sequence, the cmr switch, located upstream of the corresponding genes [ 182 ].…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%
“…Binding of c-di-GMP to Cdi2_2 positively affects cmrRST expression [ 182 ], most likely through anti-termination of transcription. Interestingly, cmrRST is also regulated by phase variation with an invertible DNA sequence, the cmr switch, located upstream of the corresponding genes [ 182 ]. CmrRST modulates colony morphology (rough or smooth) with the activation of cmrRST expression by c-di-GMP binding to Cdi2_2, promoting the development of rough colonies.…”
Section: Srnas Regulating Host-pathogen Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…difficile NAP1/B1/027 ribotype strain R20291, and an eighth in several 017 ribotype strains [ 43 , 44 ]. The identified sequences were shown to undergo inversion, and the sequence upstream of the cmrRST operon was confirmed to regulate expression of the downstream genes in a manner consistent with phase variation [ 44 , 45 ]. We subsequently showed that site-specific recombination also mediates phase variation of flagella and toxins by inversion of a genetic sequence called the “flagellar switch” [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…difficile R20291 in broth culture consists of a heterogeneous population of flg ON and OFF bacteria. Notably, RecV is also required for inversion of the cwpV switch, as well as two of the other identified invertible sequences including one shown to impact multiple phenotypes including virulence [ 40 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%